Effects of Indoor Air Quality on Human Physiological Impact: A Review - Tong Nie; Guofu Zhang; Yinan Sun; Wenhao Wang; Tianai Wang; Haoyan Duan (Buildings)
As urbanization accelerates, indoor air quality has emerged as a critical determinant of population health. To systematically evaluate the relationship between indoor air quality (IAQ) and human physiological responses, we conducted a comprehensive review of 63 experimental studies retrieved from three major databases (ScienceDirect, Google Scholar, Web of Science) spanning the years 2000–2023. This systematic review synthesizes evidence from experimental studies examining the physiological impacts of indoor air contaminants, including gaseous pollutants, particulate matter (PM), and volatile organic compounds (VOCs). Through an analysis of cardiovascular biomarkers (heart rate variability, blood pressure), respiratory parameters, and neurological indicators (electroencephalogram patterns), we identify the mechanisms linking air quality degradation to impaired physiological functioning. Our findings demonstrate that optimized ventilation systems and high-efficiency particulate filtration can mitigate exposure risks, potentially enhancing cardiovascular efficiency, pulmonary capacity, and cognitive performance. The evidence further suggests that sustained improvements for indoor environments may decrease incidence rates of respiratory pathologies and neurological disorders.